Towards a scale-bridging description of ferrogels and magnetic elastomers. (27th July 2015) - Pessot, Giorgio; Weeber, Rudolf; Holm, Christian; Löwen, Hartmut; Menzel, Andreas M
Abstract: Ferrogels and magnetic elastomers differentiate themselves from other materials by their unique capability of reversibly changing shape and mechanical properties under the influence of an external magnetic field. A crucial issue in the study of these outstanding materials is the interaction between the mesoscopic magnetic particles and the polymer matrix in which they are embedded. Here we analyze interactions between two such particles connected by a polymer chain, a situation representative for particle-crosslinked magnetic gels. To make a first step towards a scale-bridging description of the materials, effective pair potentials for mesoscopic configurational changes are specified using microscopic input obtained from simulations. Furthermore, the impact of the presence of magnetic interactions on the probability distributions and thermodynamic quantities of the system is considered. The resulting mesoscopic model pair potentials can be used to economically model the system on the particle length scales. This first coarse-graining step is important to realize simplified but realistic scale-bridging models for these promising materials.